Human biology : human anatomy and physiology - Miller, Christine; Thompson Rivers University; BC Open Textbook Project; BCcampus (Thompson Rivers University, 2020)
"This textbook is ideal for an introductory-level human biology course. It is aligned with the British Columbia Adult Basic Education learning outcomes for Provincial Level Biology, which is the equivalent of Grade 12 Anatomy and Physiology. This textbook begins with an introduction to sciences and the scientific method, and then addresses the human body in increasing scale: from biological molecules, to cells and tissues, to organs and all eleven organ systems, all with an overarching focus on health. The text employs clear writing, case studies for each chapter, interactive self-marking study activities, highlights of Indigenous knowledge and examples, a pop-up glossary, and links to resources for extending learning."--BCcampus website.
This work is licensed under the Creative Commons Attribution NonCommercial CC-BY-NC.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed on December 22, 2020).
Keywords: Human anatomy; Human physiology; Electronic books